Peran Resimen Mahasiswa dalam Ketahanan Nasional: Dinamika Pasca Reformasi di Indonesia - Fadillah, Muhammad Irfan; Ahmady, Iqbal; Ubaidullah, Ubaidullah (Journal of Political Sphere, 2024)
The Student Regiment is an organization established by the military to train students as a supporting component of national defense. This study aims to analyze the role of the Student Regiment in the context of state defense and national resilience post-reformation. The research employed a qualitative approach with a descriptive method, combining document and field studies. Data were collected through in-depth interviews with officials, members, and alumni of the Student Regiment, as well as relevant academics, supported by secondary data from literature and official documents. The findings reveal that post-reformation, the Student Regiment faced significant challenges, including the elimination of hierarchical relationships with the Indonesian National Armed Forces (TNI) and the reduction of its status to a Student Activity Unit. Internal and external dynamics, such as ambiguous government policies and concerns over politicization, influenced its role and sustainability. However, through the PSDN Law No. 23 of 2019, the Student Regiment is recognized as a supporting component of national defense. In conclusion, the Student Regiment continues to contribute to fostering national defense awareness and resilience. Nevertheless, more systematic guidance and empowerment are needed to optimize its role in Indonesias universal defense system.AbstrakResimen Mahasiswa adalah organisasi yang dibentuk oleh militer untuk melatih mahasiswa sebagai komponen pendukung pertahanan negara. Penelitian ini bertujuan menganalisis peran Resimen Mahasiswa dalam konteks bela negara dan ketahanan nasional pasca-reformasi. Penelitian menggunakan pendekatan kualitatif dengan metode deskriptif, menggabungkan studi dokumen dan lapangan. Data dikumpulkan melalui wawancara mendalam dengan pejabat, anggota, dan alumni Resimen Mahasiswa, serta akademisi terkait, didukung data sekunder dari literatur dan dokumen resmi. Hasil penelitian menunjukkan bahwa pasca-reformasi, Resimen Mahasiswa menghadapi tantangan signifikan, termasuk penghapusan hubungan hierarkis dengan TNI dan penurunan status menjadi Unit Kegiatan Mahasiswa. Dinamika internal dan eksternal, seperti kebijakan pemerintah yang ambigu dan kekhawatiran akan politisasi, memengaruhi peran dan keberlanjutan Resimen Mahasiswa. Namun, melalui Undang-Undang PSDN No. 23 Tahun 2019, Resimen Mahasiswa diakui sebagai komponen pendukung pertahanan negara. Kajian ini menyimpulkan bahwa Resimen Mahasiswa tetap berkontribusi dalam meningkatkan kesadaran bela negara dan ketahanan nasional. Namun, pembinaan dan pemberdayaan yang lebih sistematis diperlukan untuk mengoptimalkan peran organisasi ini dalam sistem pertahanan rakyat semesta.